ANALISIS EKONOMI RUMAHTANGGA USAHA TERNAK BABI DI KECAMATAN KUWUS KABUPATEN MANGGARAI BARAT (Economic household analysis on pigs farms in Kuwus Sub-District West Manggarai Regency) - Hendrikus D,. Tukan; Nautus S. Dalle; Elisabeth Y. Nugraha (JURNAL NUKLEUS PETERNAKAN, 2023)
The Study aimed to analyze 1) the contribution for pig farmers in household economy and 2) factors that effect the income of pig livestock business in increasing household economic income in Kuwus Subdistrict of West Manggarai Regency. Trial Method used is a purposive sampling in Kuwus Subdistrict. The sample determinant method was done randomly to get 20 respondents and respondents criteria the farmers pig experience at least 5 (five) years. Variables evaluated is analysis of the contribution of pig farming business to the total economic income of pig farmers' households and factors influencing the analysis business pig farm. The percentage for pig farmers against the contribution economic income household for a pig farmer in Kuwus Subdistrict West Manggarai 30.03 % with a total their income as much as Rp. 10,401,158.29/years or equivalent to Rp. 2,886,373.75/month. The factors that affect a domineering manner in economic income household for pig farmers is ownership of cattle swine, non-pig farmer income, and non-farm income while factors that significantly is age of the farmer and the widespread ose of agliculture land.